Direct quantification of hydrophobicity: a case study of environmentally relevant silver nanoparticles - Roncari, Francesco; Cordero, Salimar; Desmet, Cloé; Colpo, Pascal; Lau, Boris L. T.; Valsesia, Andrea (Frontiers in Nanotechnology, 2023)
Among the physical and chemical properties of nanomaterials, hydrophobicity is considered to play a key role in their impact on the environment. Changes in hydrophobicity resulting from abiotic and biotic processes can be used to predict the behaviours of nanoparticles (NPs) in the environment (e.g., aggregation, toxicity, and bioaccumulation). Hydrophobicity changes induced by sulfidation and natural organic matter (NOM) corona formation were evaluated by monitoring the binding rate of silver (Ag) NPs on engineered surfaces using dark-field microscopy (DFM). It was found that this DFM-based method was more capable of distinguishing the hydrophobicity of environmentally relevant AgNPs than the dye adsorption method. Under the conditions tested in this study, sulfidation and adsorption of sulfidized NOM/"lipid-free" (LF-)NOM increased the hydrophobicity of AgNPs. Both methods demonstrate the tendency of AgNPs to become more hydrophobic after sulfidation. This study shows that DFM-based methods can effectively measure the hydrophobicity of environmentally relevant NPs and have the potential to be widely used as fate predictors in the future.